THEMATIC PATTERNING TECHNIQUE ON WRITING ACHIEVEMENT AND ITS RELATIONSHIP TO ACHIEVEMENT MOTIVATION OF THE STUDENTS OF ENGLISH EDUCATION DEPARTMENT GANESHA UNIVERSITY OF EDUCATION - Juniarta, P. A. K. (International Journal of Language and Literature, 2017)
This study aimed at investigating the effect of thematic patterning technique and achievement motivation on students’ writing achievement. The subjects were the second semester students of English Education Department in the academic year 2015/2016 recruited by using cluster random sampling. The population was 7 classes, 2 classes were taken as the sample of the study. The total number of sample was 52 students who were divided into four cells of treatments. The II B class was assigned as the experimental group and II D class as the control group. The experimental group was taught by using thematic patterning technique and the control group by using conventional technique. The research design was post test only control group design by using 2x2 factorial design. There were three variables in this study, namely: independent, moderator, and dependent variables. The independent variable was thematic patterning technique and moderator variable was the students’ achievement motivation level (high and low). In another side, students’ achievement in writing paragraph was categorized as dependent variable. The instrument that was used to test the students’ achievement motivation was achievement motivation questionnaire, while the instrument used to test students’ writing achievement was writing achievement test. The analysis of data used two way Anova and then continued by post hoc testing using Tukey test. The findings of the study were: there was a significant difference in writing achievement between the students who are taught by using thematic patterning technique and those who are taught by using conventional technique. The mean score of students taught by using thematic patterning technique was higher than the mean score of students’ writing achievement for students taught by using conventional technique, there was interaction between of thematic patterning technique and the achievement motivation in learning English on students’ writing achievement.